New Benzoxazole Derivatives as Antiprotozoal Agents: In Silico Studies, Synthesis, and Biological Evaluation - Mohamed A. Abdelgawad; Mohammad M. Al-Sanea; Mohamed A. Zaki; Enas I. A. Mohamed; Shabana I. Khan; Babu L. Tekwani; Amar G Chittiboyina; Ikhlas A Khan; Tarfah Al-Warhi; Nada Aljaeed; Ohoud J. Alotaibi; Abdulsalam A. M. Alkhaldi; et al. (Journal of Chemistry)
Background. Benzoxazole derivatives have different biological activities. In pursuit of designing novel chemical entities with antiprotozoal and antimicrobial activities, benzoxazolyl aniline was utilized as a privileged scaffold of a series of (3-benzoxazole-2-yl) phenylamine derivatives, 3-benzoxazoloyl acetamide, and butyramide derivatives. Methods. These novel analogs were synthesized in straightforward simple chemistry without any quantitative chromatographic separations in reasonable yields. The biological evaluation of all target compounds as potential antimalarial, antileishmanial, antitrypanosomal, and antimicrobial agents was performed by various well-established cell-based methods. Results. Compounds 6d and 5a showed promising biological screening data. The amidation of 3-benzoxazolyl aniline 1 with the chloroacetyl functional group resulted in a good antimalarial activity and showed moderate inhibitory activities against leishmanial and trypanosomal spp. Moreover, chloroacetyl functionalization of benzoxazolyl aniline serves as a good early goal for constructing and synthesizing new antimicrobial and antiprotozoal agents. The molecular docking study rationalizes the relative inhibitory activity of compound 5a as an antimalarial agent with the deregulation of PfPNP activity which has emerged as a major mechanism of these targets.